The Existence of the State Civil Apparatus Information System (SIASN) in the Process of Determining the Decree on Promotion of Civil Servants in Agencies in the Work Area of the Regional Office XI BKN Manado - Marasut, Yulita Anuumbulan; Liando, Daud M.; Monintja, Donald K. (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
Building an integrated electronic-based government system in personnel management is very important today. Transformation of the personnel management service process based on information technology is a mandate from the Regulation of the Head of BKN Number 20 of 2008 concerning the Personnel Service Application System (SAPK). Proposals for promotion are one form of service that is currently carried out through SAPK. The Regional Office XI BKN Manado has the responsibility in the process of determining the decision letter for the promotion of Civil Servants. This study was conducted to describe the existence of SIASN in the timeliness of determining the decision letter for the promotion of Civil Servants at Agencies in the Work Area of ​​the Regional Office XI BKN Manado and what aspects cause delays in determining the decision letter for the promotion of Civil Servants. By using a qualitative design, it was found that there were slight weaknesses in the criteria for bureaucratic compliance (compliance) which can be seen from the delay in the signing stage of the decision letter for the promotion by the authorized official even though the SIASN operator had tried to be on time. The delay in signing the SKKP, although not caused by the dysfunction of the SIASN system, this obstacle still has a significant impact on the credibility of SIASN as a system designed to accelerate the promotion process.